2007
DOI: 10.1126/science.1138963
|View full text |Cite
|
Sign up to set email alerts
|

The Vaccine Adjuvant Monophosphoryl Lipid A as a TRIF-Biased Agonist of TLR4

Abstract: The inflammatory toxicity of lipopolysaccharide (LPS), a component of bacterial cell walls, is driven by the adaptor proteins myeloid differentiation factor 88 (MyD88) and Toll-interleukin 1 receptor domain-containing adapter inducing interferon-beta (TRIF), which together mediate signaling by the endotoxin receptor Toll-like receptor 4 (TLR4). Monophosphoryl lipid A (MPLA) is a low-toxicity derivative of LPS with useful immunostimulatory properties, which is nearing regulatory approval for use as a human vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
745
5
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 780 publications
(807 citation statements)
references
References 26 publications
48
745
5
9
Order By: Relevance
“…On the other hand, the blunted response of TRIF-deficient BMDC to diC14 amidine demonstrates that the action of these cationic liposomes also depends on TRIF signaling. This is consistent with the up-regulation of the expression of costimulatory molecules and the induction of IFN-b and CXCL-10 gene transcription induced by diC14 amidine in human DC since both phenomena were shown to require TRIF signaling [18,20,21].…”
Section: Stimulation Of DC By Dic14-amidine Liposomes Depends On Tlr4supporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, the blunted response of TRIF-deficient BMDC to diC14 amidine demonstrates that the action of these cationic liposomes also depends on TRIF signaling. This is consistent with the up-regulation of the expression of costimulatory molecules and the induction of IFN-b and CXCL-10 gene transcription induced by diC14 amidine in human DC since both phenomena were shown to require TRIF signaling [18,20,21].…”
Section: Stimulation Of DC By Dic14-amidine Liposomes Depends On Tlr4supporting
confidence: 84%
“…Molecular dynamics simulations of the insertion of diC14-anidine in MD2 cavity revealed that two amidine molecules do occupy a volume identical to that of one tetra-acylated lipid A molecule in the cavity (M. Lensink, personal communication) Indeed, our findings might lead to the development of diC14-amidine as a vaccine adjuvant since there is growing interest in the use of TLR4 ligands to induce T cell-mediated immunity. Interestingly, monophosphoryl lipid A, which is the TLR4 ligand in the most advanced phase of clinical development, was recently shown to be rather inefficient in inducing MyD88-dependent responses, whereas it elicits MyD88-independent TRIF-dependent cytokine production [18]. Since it has been shown that MyD88-mediated signaling is required for the induction of Th1-type immune responses [19], activation of the MyD88-dependent pathway might be required for adjuvants included in vaccines against intracellular pathogens or tumors and in anti-allergy immunotherapies.…”
Section: Stimulation Of DC By Dic14-amidine Liposomes Depends On Tlr4mentioning
confidence: 99%
“…Fourth, different transcription factors or intracellular signaling molecules might be involved in S100A8 and SAA3 signaling. For example, both lipid A and monophosphoryl lipid A bind the TLR4/MD-2 complex but monophosphoryl lipid A selectively activates only the Toll-like Interleukin 1 Receptor domain-containing adaptor-inducing interferon-b (TRIF)-TRIF-related adaptor molecule (TRAM) but not the nuclear factorkB pathway (Mata-Haro et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…21,[32][33][34][35][36][37] It was not until 2007 that the basis of the dissociation between toxicity of diphosphoryl lipid A (DPLA) on the one hand, and the potent adjuvanticity (and nontoxicity) of monophosphoryl lipid A (MPLA), on the other, became apparent. 38 Whereas DPLA, upon binding to TLR4, signals via both myeloid differentiation factor 88 (MyD88) as well as Toll-interleukin 1 receptor domain-containing adapter inducing interferon-β (TRIF)-dependent pathways, 14,[39][40][41][42][43][44][45] MPLA appears to predominantly trigger the TRIF-dependent pathway. 38 In the case of the LPS receptor TLR4, it is MyD88 that is associated with proinflammatory outcomes, while activation of TRIF-dependent pathways are correlated with immunostimulation.…”
mentioning
confidence: 99%